Synthesis and biological evaluation of new 2‑substituted‑4‑amino-quinolines and -quinazoline as potential antifungal agents. (15th September 2022) - Qin, Tian-Hong; Liu, Jian-Chuan; Zhang, Jin-Yuan; Tang, Lin-Xiu; Ma, Yan-Ni; Yang, Rui
Graphical abstract: Highlights: Potent and broad-spectrum antifungal activities against four strains of invasive fungi. Different mode of action from traditional membrane-active antifungal drugs. Low likelihood of inducing drug resistance. Excellent stability in mouse plasma. Abstract: Aiming to discover novel antifungal agents, a series of 2‑substituted‑4‑amino-quinolines and -quinazoline were prepared and characterized using IR, 1 H NMR, 13 C NMR, and HRMS spectroscopic techniques. Their antifungal activities against four invasive fungi were evaluated, and the results revealed that some of the target compounds exhibited moderate to excellent inhibitory potencies. The most promising compounds III11, III14, III15, and III23 exhibited potent and broad-spectrum antifungal activities with MIC values of 4–32 μg/mL. The mechanism studies showed that compound III11 ( N, 2-di- p -tolylquinolin-4-amine hydrochloride) did not play antifungal potency by disrupting fungal membrane, which was quite different from many traditional membrane-active antifungal drugs. Meanwhile, III11 also demonstrated a low likelihood of inducing resistance, and excellent stability in mouse plasma. In addition, some interesting structure–activity relationships (SARs) were also discussed. These results suggest that some 4‑aminoquinolines may serve as new and promising candidates for further antifungal drug discovery.